Autologous neurosensory retinal transplantation for recurrent macular hole retinal detachment in highly myopic eyes. Issue 8 (23rd April 2020) - Li, Yanzi; Li, Zhaohui; Xu, Changzhong; Liu, Yong; Kang, Xueqin; Wu, Jianhua
Abstract: Purpose: To investigate the morphological and functional reconstruction of the macular fovea after autologous neurosensory retinal transplantation for recurrent macular hole retinal detachment (MHRD) in highly myopic eyes. Methods: Ten consecutive cases of recurrent MHRD with high myopia were retrospectively reviewed. All eyes underwent pars plana vitrectomy combined with autologous neurosensory retinal transplantation and were followed up for at least 3 months after silicone oil extraction. The main outcomes were whether or not the retina was reattached and the macular hole (MH) was closed, morphological changes in the retinal graft, best‐corrected visual acuity (BCVA), the sensitivity threshold and blood flow signal in the macula. Results: At the one month postoperative visit, there was an obvious boundary between the graft and the surrounding retinal tissue, and some retinal structural layers could be seen in the graft on optical coherence tomography scans. At the final follow‐up, eight eyes (80%) showed retinal reattachment and closure of the MH. Optical coherence tomography revealed blurring of the boundary between the graft and surrounding retinal tissue and that the retinal structure in the graft was disordered. The MH was not closed in two eyes (20%), in one case because of partial displacement of the graft and in the other because of incomplete coverage of the MH as a result of a smaller graft. The post‐BCVA was significantly better than the pre‐BCVA (1.32 ± 0.33 versus 2.01 ± 0.29 logMAR; p = 0.000, paired t ‐test). Conclusion: Autologous neurosensory retinal transplantation can be an effective treatment for recurrent MHRD in highly myopic eyes. 'Fusion' between the neurosensory retinal graft and the original retinal tissue may be the mechanism involved in the closure of the MH and reconstruction of the macular fovea.